Design and synthesis of quasi-diastereomeric molecules with unchanging central, regenerating axial and switchable helical chirality via cleavage and formation of Ni(II)–O and Ni(II)–N coordination bonds - Soloshonok, Vadim A (Beilstein-Institut, 2012)
We describe herein the design and synthesis of asymmetric, pentadentate ligands, which are able to coordinate to Ni(II) cations leading to quasi-diastereomeric complexes displaying two new elements of chirality: stereogenic axis and helix along with configurational stabilization of the stereogenic center on the nitrogen. Due to the stereocongested structural characteristics of the corresponding Ni(II) complexes, the formation of quasi-diastereomeric products is highly stereoselective providing formation of only two, (R(a)*,M(h)*,R(c)*) and (R(a)*,P(h)*,R(c)*), out of the four possible stereochemical combinations. The reversible quasi-diastereomeric transformation between the products (R(a)*,M(h)*,R(c)*) and (R(a)*,P(h)*,R(c)*) occurs by intramolecular trans-coordination of Ni–NH and Ni–O bonds providing a basis for a chiral switch model.